Break the pattern the science of transformational value creation - Songip, Ahmad Rahman (Canada Blackcard Books, 2018)
This book is written based on my own personal journey in doing and managing research and innovation in the university and the corporate world. Upon graduation with a Doctorate in CHemical Engineering from Kyoto University in the early 199s, I embarked on an ambitious research program after getting huge grants from the Malaysian government. Unfortunately, research and innovation ecosystem in Malaysia was only in the beginning stages at that time. Frustrated with so many bureaucratic procedures that slowed down my research progress, I decided to take unpaid leave and joined a leading chemical company as a general manager. My industrial experience exposed me to a totally different sphere: the world of management. It was an alien knowledge and skill to me. So, I was on a very steep curve learning the ropes while managing five companies within the chemical division of the listed company. i found out that it was much more exciting feat, creating value by managing innovation compared to doing research in the laboratory. I was forced to cut short my industrial stint due to the Asian financial meltdown in the late 1990s. Upon returning back as an academic, i offered myself to help out the university to turn around ailing business units. I also started teaching modules on creative problem-solving, innovation management, project management, and entrepreneurship management as well as supervising graduate students in the area of innovation management. Equipped with practical experiences from industry and successfully re-engineered ailing entities in the university, I started to offer training and consulting services in industry based on the concept of Break the Pattern - the science of transformational value creation - together with my colleagues and students. the most challenging assignment to date was conducting a series of workshops, based on the content of this book, with the current and future leaders of the institution of higher learning in Malaysia in Akademi Kepimpinan Pendidikan Tinggi (AKEPT), the learning arm of the Ministry of Higher Education Malaysia. I was grilled, challenged, and scrutinized by the most experiences academic leaders; some of them were senior professors and deans of management and business schools as well as heads of corporate strategy departments. Thanks to the Almighty God, I have survived! -- Preface.
Part I: Break the pattern -- Part II: Shaping the context -- Part III: Input, output, and feedback -- Part IV: Execution -- The way forward -- References.
Keywords: Organizational change; Organizational change -- Management; Corporate turnarounds -- Management